Compromised quality of life in patients with both Type 1 diabetes mellitus and coeliac disease. Issue 7 (25th April 2013) - Bakker, S. F.; Pouwer, F.; Tushuizen, M. E.; Hoogma, R. P.; Mulder, C. J.; Simsek, S.
Abstract Aims Type 1 diabetes mellitus and coeliac disease are two chronic illnesses associated with each other. Both diseases and their treatments can seriously impair quality of life. The objective of the present study was to investigate health‐related quality of life in adult patients diagnosed with both Type 1 diabetes and coeliac disease and compare this with healthy control subjects and control subjects who have Type 1 diabetes only. Methods A generic measure of health‐related quality of life (RAND‐36) and a measure of diabetes‐specific quality of life (DQOL) questionnaires were sent to patients diagnosed with both Type 1 diabetes and coeliac disease. The control group consisted of patients with Type 1 diabetes without coeliac disease matched for age, gender and socio‐economic status. Generic quality of life scores were compared with data from healthy Dutch control subjects. Results Fifty‐seven patients with Type 1 diabetes and coeliac disease were included and no associations between clinical characteristics and quality of life were observed. Women reported a lower quality of life in social functioning, vitality and mental health than men (all P < 0.05). A lower diabetes‐specific quality of life was observed regarding diabetes‐related worries and social worries in patients with Type 1 diabetes and coeliac disease compared with patients with Type 1 diabetes. Compared with healthy control subjects, quality of life in patients with Type 1 diabetes and coeliac disease was significantly lower, particularly social functioning (Cohen's d = 0.76) and general health perception (Cohen's d = 0.86). Conclusions The additional diagnosis of coeliac disease and treatment by gluten‐free diet in adult patients with Type 1 diabetes has a considerable, negative impact on quality of life and diabetes‐specific quality of life. Women are particularly affected and social functioning and general health perception is compromised.